Implementasi Kurikulum Merdeka Belajar di MA Nahdlatul Ulama’: Putri Wulandari, Muhammad Lutfi* - Wulandari, Putri; Lutfi, Muhammad (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
The purpose of this study is to investigate the implementation of the "Merdeka Belajar" (Freedom of Learning) curriculum at MA Nahdlatul Ulama and the challenges experienced. This research employs a qualitative descriptive method, where data is obtained through in-depth interviews and field observations. The findings of this study indicate that the implementation of the Merdeka Belajar curriculum at MA Nahdlatul Ulama begins with education and training. Subsequently, meetings are held and teams are formed for the development of the School Operational Curriculum (Kurikulum Operasional Satuan Pendidikan or KOSP). Learning is carried out based on project-based teaching modules (both short-term and long-term projects), and instruction is tailored to the characteristics of the students. Curriculum evaluation is conducted through diagnostic, formative, and summative assessments, with learning outcomes reported through report cards. Challenges in the implementation of the Merdeka Belajar curriculum include not all teachers fully understanding the curriculum. Insufficient literacy, references, and understanding among teachers in utilizing technology also serve as hindering factors in the implementation of the Merdeka Belajar curriculum.